Perspektif Hukum Positif dan Hukum Islam di Indonesia terhadap Perkawinan Beda Agama - Eneng Juandini (Departement of Mathematics Education, 2023)
Marriage is a very important thing in the reality of human life. The reality in people's lives that interfaith marriages occur as a reality that cannot be denied, of course, really ignores the existence of applicable laws and regulations. Regulatively, interfaith marriages in Indonesia do not have legal force because Law Number 1974 Concerning Marriage Chapter 1 article 2 paragraphs 1 & 2, Compilation of Islamic Law article 40 paragraph c and article 44 of the MUI Fatwa have prohibited interfaith marriages. What are the perspectives of positive law and Islamic law on interfaith marriage from the point of view of the similarities and differences between the two laws. The method in this study uses a qualitative method in the form of literature review. The data sources used in this research review consist of two sources (primary and secondary). The main sources used in this study were KHI (Compilation of Islamic Law) and RI Law No. 1 of 1974, and UU No. 23 of 2006 while the secondary sources used in this study were books and scientific writings that had links with the object being studied. Based on the perspective of positive law and Islamic law, interfaith marriage is seen as having greater harm than benefit. Doing interfaith marriages means ignoring the laws and regulations that apply in this country. The logical consequence is that there will be various problems in the household so that it is impossible to create a sakinah family.